Dynamics of Bioplastics Development in Indonesia - Qinan Maulana Binu Soesanto; Dian Prihadyanti; Hartiningsih Hartiningsih; Trina Fizzanty (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2016)
Increase in consumption of conventional plastics lead to environmental problems. Therefore, some efforts are needed to overcome it, one of them by using bioplastics. However, in Indonesia, companies engaged in bioplastics sector are still rarely found. Without the readiness of the bioplastics industry in Indonesia, development of bioplastics which ends to solve environmental problems cannot be realized. Through Socio-Technical Systems (STS) approach with Multi Level Perspective framework, this Papper analyze the dynamics of the transition of bioplastics in Indonesia. The results show the presence of pressure from landscape to underdeveloped niche, regime actors would give respond by modifying path development from its innovation activities. In other words, bioplastics in Indonesia has not yet experiencing a transition to replace conventional plastics. Precisely, technology in regime level experiencing change by developing additive plastic. However, there are several things that hinder further development of the niche, which include the high price of bioplastics and implementation of regulations related with incentives and disincentives and there is no coordination and shared vision between actor in niche level.